A novel concept of posterior decompression and instrumented fusion with selective lordotic correction for cervical ossification of the posterior longitudinal ligament. (October 2019) - Katsumi, Keiichi; Hirano, Toru; Watanabe, Kei; Ohashi, Masayuki; Mizouchi, Tatsuki; Wakasugi, Masashi; Makino, Tatsuo; Yamazaki, Akiyoshi; Endo, Naoto
Highlights: We introduced a novel concept of PDF for cervical K-line (−) OPLL. The mean recovery rate of JOA score at the final follow-up was 70.9%. This method can achieve posterior shift of the spinal cord while preventing C5 palsy. Abstract: Purpose: The recovery rate of Japanese Orthopedic Association (JOA) score with K-line (−) cervical ossification of the posterior longitudinal ligament (OPLL) for posterior decompression with in-situ fusion (PDF) tends to be lower than that of anterior decompression with fusion (ADF). However, ADF is a technically demanding operation and has ADF-specific complications. This prospective report introduced a novel concept of PDF with selective lordotic correction as well as prophylactic foraminal decompression. Methods: Six consecutive patients (four men and two women; mean age, 61.8 years) were included. PDF was performed, attempting to create cervical lordosis to acquire a posterior shift of the spinal cord, while preventing postoperative C5 palsy by prophylactic facetectomy and selective lordotic correction. Results: The mean recovery rate of JOA score at the final follow-up was 70.9 ± 20.3%. The mean C2–C7 angle preoperatively and at final follow-up was 5.5 ± 3.9° and 12.2 ± 4.8°, respectively. No symptomatic nerve root palsy, except one case with transient C7 root iatrogenic palsy, was found. Conclusions: A novel concept of PDF with selective lordotic correction obtained recovery rates of JOA scores comparable to those of ADF. We believe that this method can improve PDF outcomes in patients with K-line (−) OPLL.